Particle board and hardboard - Akers, L. E. (Pergamon series of monographs on furniture and timber, 1966)
Pergamon Series of Monographs on Furniture and Timber, Volume 4: Particle Board and Hardboard focuses on particle boards, which are described as a sheet material manufactured from small pieces of wood or other ligno-cellulosic materials agglomerated by use of an organic binder together with agents such as heat, pressure, moisture, and catalyst. This book is divided into two parts. Part I concentrates on the types; methods of manufacture; physical and strength properties; tests, test methods, and quality evaluation; handling and machining; utilization in furniture and building of particle board.